2011
DOI: 10.3928/01484834-20110228-01
|View full text |Cite
|
Sign up to set email alerts
|

Predicting NCLEX-RN Success in a Diverse Student Population

Abstract: Many schools of nursing have implemented standardized testing using platforms such as those developed by Assessment Technologies Institute (ATI) to better prepare students for success on the National Council Licensure Examination for Registered Nurses® (NCLEX-RN). This study extends and replicates the research on standardized testing to predict first-time pass success in a diverse student population and across two prelicensure program types. The final sample consisted of 589 students who graduated between 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The only other significance found was between nursing course grades in medical surgical nursing and nursing pathophysiology (Alameida et al, 2011).…”
Section: Nursing Program Progressionmentioning
confidence: 91%
See 1 more Smart Citation
“…The only other significance found was between nursing course grades in medical surgical nursing and nursing pathophysiology (Alameida et al, 2011).…”
Section: Nursing Program Progressionmentioning
confidence: 91%
“…This would support the ATI testing system which is also a standardized evaluation of NCLEX-RN readiness. Alameida et al (2011) at San Francisco State University looked at predicting NCLEX-RN success using the ATI RN comprehensive predictor test score and the ATI predictor probability of first-time NCLEX-RN pass. These researchers found a significant relationship between NCLEX-RN success on the first try and the ATI variables.…”
Section: Relevance To Literaturementioning
confidence: 99%
“…Studies have repeatedly shown that an exit examination prior to graduation may significantly predict NCLEX-RN success. 4,6,8 However, according to Spurlock 9 and Spurlock and Hunt, 7 these high-stakes examinations are able to identify students who are likely to pass the NCLEX-RN, but are less likely to identify students with a potential failure of the NCLEX-RN. Such research suggests that there may be insufficient evidence to support restricting graduation after the failure of a high-stakes exit examination.…”
Section: Legalmentioning
confidence: 97%
“…Preparing for exit examinations and remediating in areas of weakness help students understand key concepts prior to taking the NCLEX-RN. 6 The data collected are helpful for curriculum development and revision. 2 Furthermore, with a standardized format, faculty can compare their students' performances to other students across the nation.…”
Section: Considerationsmentioning
confidence: 99%
See 1 more Smart Citation